2005
DOI: 10.1016/j.chembiol.2005.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Iteratively Acting Glycosyltransferases Involved in the Hexasaccharide Biosynthesis of Landomycin A

Abstract: Detailed studies on the biosynthesis of the hexasaccharide side chain of landomycin A, produced by S. cyanogenus S136, revealed the function of each glycosyltransferase gene of the biosynthetic gene cluster. Analyses of generated mutants as well as feeding experiments allowed us to determine that LanGT2 and LanGT3 catalyze the attachment of one sugar, whereas LanGT1 and LanGT4 attach two sugars during landomycin A biosynthesis. The generation of a lanZ2 deletion mutant provided evidence that LanZ2 is controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 17 publications
2
61
0
1
Order By: Relevance
“…Iterative use of glycosltransferases, however, is not unprecedented in natural product biosynthesis. In landomycin A biosynthesis, LanGT1 (an olivosyltransferase) and LanGT4 (an rhodinosyltransferase) act twice, with each transferring two of the sugars (olivose and rhodinose) found in the hexasaccharide portion of the landomycin A structure (24). Ramoplanin, like mannopeptimycin, contains an O-linked di-mannose, and in the ramoplanin gene cluster there is only one glycosyltransferase (Ram29) (11).…”
Section: Resultsmentioning
confidence: 99%
“…Iterative use of glycosltransferases, however, is not unprecedented in natural product biosynthesis. In landomycin A biosynthesis, LanGT1 (an olivosyltransferase) and LanGT4 (an rhodinosyltransferase) act twice, with each transferring two of the sugars (olivose and rhodinose) found in the hexasaccharide portion of the landomycin A structure (24). Ramoplanin, like mannopeptimycin, contains an O-linked di-mannose, and in the ramoplanin gene cluster there is only one glycosyltransferase (Ram29) (11).…”
Section: Resultsmentioning
confidence: 99%
“…While LandGT1 is responsible for the transfer of the second and fifth sugar moiety, LanGT4 transfers both rhodinoses into the third and sixth positions. [16] Most recently, LanGT2 was identified to catalyze the first glycosylation step (D-olivosyl), [17] and a targeted gene inactivation experiment on lanGT3 showed that the corresponding glycosyltransferase LanGT3 is an olivosyltransferase. [18] LanGT3 is most likely responsible for the attachment of the fourth sugar, which is the key step that distinguishes the biosyntheses of LaA and LaE.…”
Section: Introductionmentioning
confidence: 99%
“…PnxGT2 belongs to glycosyltransferase family 28 and shows similarity to many O-glycosyltransferases, including LanGT1 (62%), LanGT3 (55%) and LanGT4 (47%) in landomycin biosynthesis and AtG1 (50%) in AT2433 biosynthesis. Because LanGT1 and LanGT4 were confirmed to be used iteratively in landomycin biosynthesis, 44 PnxGT2 was proposed to similarly catalyze two glycosylations to complete the trisaccharide formation in FD-594 biosynthesis.…”
Section: Glycosyltransferases and Methyltransferasesmentioning
confidence: 99%